Puerarin blocks transient outward K+ current and delayed rectifier K+ current in mice hippocampal CA1 neurons - Zhang Guang-Qin; Hao Xue-Mei; Zhou Pei-Ai; Wu Cai-Hong; Dai De-Zai (Acta Pharmacologica Sinica, 2016)
Aim: To study the effects of puerarin (Pue) on IA and IK in mouse hippocampal neurons. Methods: The whole cell patch clamp techniques were used. Results: Pue reduced the amplitude of IA and IK, in a concentration-dependent, but not rate- or use-dependent manner (IC50 were 461 micromol/L and 215 micromol/L, respectively). Pue (0.5 mmol/L) shifted the steady state activation curves of IA and IK to positive and negative potentials (Vh about 20.6 mV and 28.6 mV) respectively, but inactivation curves of IA were not affected by Pue. Conclusion: Pue inhibited IA and IK in mouse hippocampal CA1 neurons and its blocking effect on I(K) was much stronger than on IA.